Increasing Motivation in Learning Science by the Implementation of Think Pair Share Cooperative Learning Models Online in Kelas IX-1 in SMP Negeri 4 Padangsidimpuan - Nirwati (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
This classroom action research was conducted to find out how the implementation of the Think Pair Share Cooperative learning model is significant to increase students' motivation in learning science online in Kelas IX-1 in SMP Negeri 4 Padangsidimpuan. This research is a descriptive qualitative study conducted in two cycles with 22 students as participants and the researcher herself acted as a participant-observer in this study. Data collection techniques were carried out through observation and document analysis, and the findings were then analyzed qualitatively based on relevant theories used in the study. This study found that the implementation of the Think Pair Share model can improve students’ learning outcomes in science in Kelas IX-1 in SMP Negeri 4 Padangsidimpuan. The implementation of the teaching method also improves students' ability in speaking and in critically thinking. However, the implementation of online classes expects the teacher's maximum effort in motivating students to involve in learning activities. Technical problems regarding online learning activities are still found challenging for teachers and students. Therefore, further study is recommended regarding the issues to find satisfactory findings.